Draft Annual Plan 1980-81 with Component Plan for Scheduled Castes Government of Manipur - Planning Commission (Planning Commission, 1980)
The State of Manipur literally meaning "the land of Jewels" consists of valley of about 2230 sq. kms. in area situated at a height of 2,500 feet and surrounded by hilly extract which is about nine times the area of the valley i.e. 20126 sq. kms. Manipur is situated in the north eastern region of the country bordered with Burma in the coast, Nagaland in the north, Assam in the west, and Mizoram in south. The State is landlocked. Rows and rows of rolling hills cover 90% of the area of this State surrounding the heart land of the valley in the centre and forming a preventive barrier that isolates Manipur from the neighbouring sister States and Union Territories of the country.
Government of Manipur, Planning Department